Carbonate Facies and Sedimentation of the Klapanunggal Formation in Cibinong, West Java - Praptisih, Praptisih; Kamtono, Kamtono (Indonesian Journal on Geoscience, 2014)
DOI:10.17014/ijog.v1i3.196The limestone of Klapanunggal Formation is well exposed in the area of Cibinong and its surrounding,West Java. Detailed Observation of carbonate rock has been conducted in this area and aims to studythe carbonate facies and its growth environment. The method used in the field is the detailedinvestigation, while mikropaleontology and petrogaphic analysis conducted in the laboratory. Theresult of this study indicate that the carbonate rocks in the study area consists of four facies. namely:(1) boundstone facies, (2) packstone facies, (3) rudstone facies, and (4) limestone breccia facies. Basedon these data be interpreted that the boundstone facies was deposited in the reef front to reef crestenvironment, packstone facies developed on the lower slope, upper slope, and back-reef lagoonenvironment. Rudstone facies formed on the reef front, and breccia limestone facies were formed inthe lower slope. Geographically, the position of the carbonate body environment that is at the reeffront, upper slope and lower slope is expected to be in the North – North East while the reef crest andback reef lagoon is on the South – Southwest.